Expression from the murine p53 promoter is mediated by factor binding to a downstream helix-loop-helix recognition motif. - Ronen, D (1991)
Expression of the p53 gene plays an important role in the regulation of cellular proliferation and malignant transformation. Overexpression of mutant forms of p53 is in fact a common feature of many transformed cells. Studies dealing with the transcriptional regulatory regions of the p53 gene indicate that, unlike most promoters transcribed by RNA polymerase II, the p53 promoter contains no TATA-like sequence upstream of the transcription start site. Here we demonstrate that the murine p53 promoter contains a cis-acting element that maps downstream to the transcription initiation site. The integrity of this element is required for high-level expression from the promoter in transformed cells. By DNase I protection and mobility-shift analysis, we show that a nuclear factor binds to this downstream element through the consensus recognition sequence for the helix-loop-helix (HLH)-containing proteins of the myc/MyoD family of transcriptional regulators. We propose that the activity of one or more members of this family of transcription factors is an important determinant in the expression of p53 and that at least one level of p53 overexpression in transformed cells may thus be due to aberrant expression of the relevant factor(s). Furthermore, the possibility that the regulation of expression of p53 occurs, in part, by means of a potential HLH-containing factor provides a possible mechanism for the suppression of proliferation by the MyoD family of transcriptional regulators.